Colliding Impulsive Waves in Succession - Mustafa, Halilsoy (Physical Review -Series d-, American Physical Society (APS), 1990)
We formulate the initial-value problem for two colliding trains of impulsive gravitational waves. In the absence of a global, exact solution we show that in a region lying between the singularity u'+ U'= 1 and the wave trains, the solution is still the well-known Khan-Penrose solution.
The file in this item is the publisher version (published version) of the article.
Keywords: mpulsive gravitational waves; Khan-Penrose solution.; general relativity